2014
DOI: 10.1089/ars.2013.5587
|View full text |Cite
|
Sign up to set email alerts
|

CaMKKβ-Dependent Activation of AMP-Activated Protein Kinase Is Critical to Suppressive Effects of Hydrogen Sulfide on Neuroinflammation

Abstract: Aims: The manner in which hydrogen sulfide (H 2 S) suppresses neuroinflammation is poorly understood. We investigated whether H 2 S polarized microglia to an anti-inflammatory (M2) phenotype by activating AMPactivated protein kinase (AMPK). Results: Three structurally unrelated H 2 S donors (5-(4-hydroxyphenyl)-3H-1,2-dithiocyclopentene-3-thione [ADT-OH], (p-methoxyphenyl) morpholino-phosphinodithioic acid [GYY4137], and sodium hydrosulfide [NaHS]) enhanced AMPK activation in BV2 microglial cells in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 51 publications
3
88
1
Order By: Relevance
“…In addition, CaMKK-betadependent AMPK activation causes NaHS suppression of neuroinflammation [39]. Hence, it is likely that the model shown here may result from NaHS and ROCK's effects upon activated …”
Section: Discussionmentioning
confidence: 87%
“…In addition, CaMKK-betadependent AMPK activation causes NaHS suppression of neuroinflammation [39]. Hence, it is likely that the model shown here may result from NaHS and ROCK's effects upon activated …”
Section: Discussionmentioning
confidence: 87%
“…Recently we showed that H 2 S donors activated AMPK in several cell types [7,23]. In this study, ADT at the protective dose up- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 regulated AMPK activation following myocardial I/R.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that ADT [5-(4-methoxyphenyl)-3H-1,2-dithiole-3-thione], a clinical drug approved in China and Europe, protected against cerebral ischemia as a slow-releasing organic H 2 S donor [6]. We also reported that ADT-based H 2 S donors activated AMPK more robustly than the well-established AMPK activator metformin [7]. However, it remains unknown if H 2 S donors act through AMPK activation to protect against myocardial I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured osteoblasts, activation of AMPK inhibits H 2 O 2 -induced cell apoptosis [16,17]. Recent studies have shown that H 2 S could activate AMPK [18,19], however its role in H 2 S-mediated cyto-protective activity is not fully understood.…”
Section: Introductionmentioning
confidence: 99%